DETERMINAN KECURANGAN LAPORAN KEUANGAN: PENGUJIAN TEORI FRAUD TRIANGLE - Yuvita Avrie Diany; Dwi Ratmono (Diponegoro Journal of Accounting, 2014)
The purpose of this paper is to examine factors which affect (determinants) financial statement fraud. Detection of financial statement fraud is using Fraud Triangle theory. Based on Fraud Triangel theory there are three variables hypothesized affect fraud which are pressure, opportunity, and rationalization. This study use data of 27 companies which did financial statement fraud and 27 other companies matched. Data can be collected from annual report published by website IDX. Data then analized using logistic regression analysis. The result of this study shows significant positive relation between pressure and opportunity with financial statement fraud. While rationalization can’t be proved to financial statement fraud yet.